Pharmacological treatments for gambling disorder: a current review of literature - Aktan Mutlu, Elif; Yontar, Gözde; Aksoy, Begüm Gökhan (Journal of Dependence, 2025)
This narrative review aims to examine pharmacological treatment modalities for gambling disorder (GD) by analyzing recent literature and identifying significant trends in the field. A thorough examination of relevant literature, focusing primarily on recent studies and reviews, in order to identify significant pharmacological treatment approaches and current trends. Results: The review identifies several pharmacological approaches for GD, including opioid antagonists, serotonergic agents, dopaminergic modulators, glutamatergic agents, and mood stabilizers. Recent studies suggest that opioid antagonists such as naltrexone and nalmefene show promise in reducing gambling urges and behaviors. Additionally, serotonergic agents like selective serotonin reuptake inhibitors (SSRIs) have demonstrated efficacy in alleviating the impulsivity and compulsivity associated with GD. Dopaminergic and glutamatergic agents, while showing some potential, require further investigation for their role in GD treatment. Mood stabilizers, particularly lithium, appear to be beneficial, especially in individuals with co-occurring bipolar affective disorder. Pharmacological interventions play a crucial role in the management of GD, with opioid antagonists and SSRIs emerging as promising options. However, further research is needed to elucidate the optimal pharmacotherapeutic approach and develop more targeted treatments for GD. Integration of pharmacotherapy with psychotherapeutic interventions may enhance treatment outcomes for individuals with GD.
Keywords: Gambling disorder; addictive behaviors; glutamatergic agents; mood stabilizers